2021
DOI: 10.3390/foods10102262
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pesticide Residues in Spanish Honey Measured by QuEChERS Method Followed by Liquid and Gas Chromatography–Tandem Mass Spectrometry

Abstract: In the current study, the QuEChERS extraction method with slight modifications, followed by liquid and gas chromatography–tandem mass spectrometry, was applied for the determination of 399 pesticide residues in 91 raw honey samples from northeastern Spain. The quality control procedure established in Document No. SANTE/12682/2019 was successfully followed: the responses in reagent blank and blank honey samples were below 30% of the reporting limit (0.01 mg kg−1) for all analysed compounds, the correlation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This leads to the frequent application of doses higher than those recommended, and it is highly likely that acaricide residues appear in the different beehive products (Nozal, Imaz, Bernal, Nieto, Higes, & Bernal, 2021) including honey. Indeed, acaricide residues have been found in honeys from different countries (Almeida, Oloris, Faria, Ribeiro, Cantini, & Soto, 2020;Bajuk et al, 2017;Calatayud-Vernich, Calatayud, Simó, & Picó, 2016;Chiesa et al, 2016;Gaweł et al, 2019;Jiménez, Bernal, & Atienza, 1996;Kamel, & Al-Ghamdi, 2006;Kumar, Gill, Bedi, & Kumar, 2018;Lasheras, Lázaro, Burillo, & Bayarri, 2021;Panseri et al, 2020;Lazarus et al, 2021;Martel., Zeggane, Aurières, Drajnudel, Faucon, & Aubert, 2007;Notardonato, Avino, Cinelli, & Russo, 2014;Notardonato et al, 2016;Panseri et al, 2020;Rafique et al, 2018;Rial-Otero, Gaspar, Moura, & Capello, 2007;Shamsipur, Yazdanfar, & Ghambarian, 2016;Shendy, Al-Ghobashy, Mohammed, Alla, & Lofty, 2016;Zheng et al, 2018), and maximum residue levels have been established by regulatory agencies like the Directorate-General for Health and Food Safety of the European Commission see Table 1; European Union Pesticide Database, 2022) to protect the consumer´s health.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the frequent application of doses higher than those recommended, and it is highly likely that acaricide residues appear in the different beehive products (Nozal, Imaz, Bernal, Nieto, Higes, & Bernal, 2021) including honey. Indeed, acaricide residues have been found in honeys from different countries (Almeida, Oloris, Faria, Ribeiro, Cantini, & Soto, 2020;Bajuk et al, 2017;Calatayud-Vernich, Calatayud, Simó, & Picó, 2016;Chiesa et al, 2016;Gaweł et al, 2019;Jiménez, Bernal, & Atienza, 1996;Kamel, & Al-Ghamdi, 2006;Kumar, Gill, Bedi, & Kumar, 2018;Lasheras, Lázaro, Burillo, & Bayarri, 2021;Panseri et al, 2020;Lazarus et al, 2021;Martel., Zeggane, Aurières, Drajnudel, Faucon, & Aubert, 2007;Notardonato, Avino, Cinelli, & Russo, 2014;Notardonato et al, 2016;Panseri et al, 2020;Rafique et al, 2018;Rial-Otero, Gaspar, Moura, & Capello, 2007;Shamsipur, Yazdanfar, & Ghambarian, 2016;Shendy, Al-Ghobashy, Mohammed, Alla, & Lofty, 2016;Zheng et al, 2018), and maximum residue levels have been established by regulatory agencies like the Directorate-General for Health and Food Safety of the European Commission see Table 1; European Union Pesticide Database, 2022) to protect the consumer´s health.…”
Section: Introductionmentioning
confidence: 99%
“…Due to pest control treatments of hives or through the transfer of contaminated beeswax, veterinary medicinal drugs (such as antibiotics banned in beekeeping or legal acaricides) can be found in honey [26][27][28][29][30]. At the same time, honey must not contain traces of metals or the heavy metal content should be minimal, as defned by EU food regulations [8,[31][32][33].…”
Section: Potential Health Risks Of Consuming Honeymentioning
confidence: 99%
“…Long-term consumption of pesticide-contaminated honey may lead to a range of health issues, including neurological disorders, hormonal imbalances, and an increased risk of certain cancers. As those pesticides accumulate in the human body over time, their efects can be insidious, emphasizing the urgency of monitoring and controlling pesticide use in beekeeping practices [27,31,33,53,54].…”
Section: Honey Contaminationmentioning
confidence: 99%
“…Pesticide analysis supported LC-MS/MS and GC-MS/MS instrumentation that permits the determination of widespread agricultural pesticides worldwide such as chlorpyrifos, imidacloprid, dimethoate, and tebuconazole (19) . The QuEChERS extraction strategy with slight alterations, taken after by fluid and gas chromatographytandem mass spectrometry, was connected for the assurance of pesticide buildups in crude nectar tests from northeastern Spain was performed by Lasheras et al and identified Chlorfenvinphos and coumaphos buildups (20) . Xiao et al detected carbendazim and pyrethroids among the honey samples of China using a modified version of the QuEChERS multi-residue method (21) .…”
Section: Sample Analysismentioning
confidence: 99%